APPLICATION OF THE CONCEPT OF TOTAL QUALITY MANAGEMENT BUSINESS COMPETITIVENESS - Rosdaniah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The development of the world economy greatly influences business competition as a whole and business competition is one of the important factors in running a country's economy. Business development is experiencing changes due to several factors that underlie business competition, namely globalization, trade growth and international competition. The high level of competition will directly or indirectly affect their business performance, globalization and technology will be a threat to the success of a business venture in a company. The company's success is very dependent on management's willingness to abandon traditional management approaches and use a better management style approach, namely by using integrated quality management or what is called the Total Quality Management (TQM) approach.